(untitled) (Studia austriaca, 2014)
Short stories like Doktor Gräsler Badearzt, Casanova Heimfahrt, Traumnovelle, Spiel im Morgengrauen and cinematographic adaptations like the ones by Roberto Faenza (1990), Edouard Niermans (1992), Mario Bianchi (1989) and Götz Spielmann (2001) show various examples of female and male imaginative sexual/gender identity: strong emancipated women, weak and subordinated men and ambiguous beings like the chameleon couple Leopoldine/Willi Kasda. In these contexts literature and film no longer define the female imaginative construction as a product of male imagination, but rather as a progressive female effort to become independent from traditional male stereotypes.